Level of phospho-STAT3 (Tyr705) correlates with copy number and physical state of human papillomavirus 16 genome in cervical precancer and cancer lesions - Shukla, Shirish (PLoS One, 2019)
Our earlier studies indicated an important role of inducible transcription factor STAT3 in the establishment of persistent infection of human papillomavirus (HPV) type 16 and promotion of cervical carcinogenesis. Since HPV load and its physical state are two potential determinants of this virally-induced carcinogensis, though with some exceptions, we extended our study to examine the role of active STAT3 level in cervical precancer and cancer lesions and it’s association with HPV viral load and physical state. An elevated level of active STAT3 was measured by assessing phospho-STAT3-Y705 (pSTAT3), in tumor tissues harboring higher viral load irrespective of the disease grade. Physical state analysis of HPV16 by assessing the degree of amplification of full length E2 and comparing it with E6 (E2:E6 ratio), which predominantly represent episomal form of HPV16, revealed low or undetectable pSTAT3. A strong pSTAT3 immunoreactivity was found in tissues those harbored either mixed or predominantly integrated form of viral genome. Cumulative analysis of pSTAT3 expression, viral load and physical state demonstrated a direct correlation between pSTAT3 expression, viral load and physical state of HPV. The study suggests that there exists a strong clinical correlation between level of active STAT3 expression and HPV genome copy number, and integrated state of the virus that may play a pivotal role in promotion/maintanence of tumorigenic phenotype.